RETENTION OF REMOTE PUBLIC HEALTH CENTER DOCTOR IN NORTH KONAWE DISTRICT - Tambun, Sondang Whita Kristina; Bashabih, Masyitoh (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: Remote public health centers (PHCs) have the highest proportion of PHCs without doctors, with Southeast Sulawesi Province ranking fifth in this regard. PHCs serve as the main gateway to health services in rural and remote areas. Despite its high fiscal capacity and provision of support for medical education and incentives, North Konawe District has not succeeded in retaining doctors in its public health centers. Aims: This study aims to analyze factors that influence the retention of doctors in remote PHCs in the North Konawe District. Methods: This qualitative study employed a case study design, involving in-depth interviews with 14 informants and a review of six documents. Results: Factors affecting doctor retention in the North Konawe District include individual factors, work factors, living environment factors, and health system factors. Conclusion: Doctors in remote PHCs in North Konawe District are Ministry of Health placement doctors working on temporary contracts. Strategies to improve the retention of doctors in remote PHCs include improving living conditions in remote areas, supporting job opportunities for doctors' spouses, recruiting doctors early in their careers, implementing government disincentive policies, building PHCs with official housing, requiring mandatory service for recipients of medical education scholarships, and developing doctor attendance information systems. Keywords: Doctor, PHC, remote area, retention.